Redesign of Facility Layout at Pelangi Advertising Printing Using the SLP Method - Syafirman Pramija; Meipen Meipen (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
This paper aim is to investigate the work system for printing service and redesign facility layout improvement. A case study was conducted in small company namely Pelangi Advertising Printing. The Systematic Layout Planning (SLP) was adopted in this paper. The input data and activities in the SLP process are as follows: material flow, activity relationship, string diagrams, area requirement, area available, space relationship diagrams, modification consideration and practical limitations. The results of this study indicated the application of SLP in case study company can increase in facility layout efficiency from 96.7% to 98.5%. The redesign facility layout result was more effective than the initial layout.